Structure and Properties of Nanocomposites Formed by the Occlusion of Block Copolymer Worms and Vesicles Within Calcite Crystals. (28th January 2016) - Kim, Yi‐Yeoun; Semsarilar, Mona; Carloni, Joseph D.; Cho, Kang Rae; Kulak, Alexander N.; Polishchuk, Iryna; Hendley, Coit T.; Smeets, Paul J. M.; Fielding, Lee A.; Pokroy, Boaz; Tang, Chiu C.; Estroff, Lara A.; et al.
Abstract : This article describes an experimentally versatile strategy for producing inorganic/organic nanocomposites, with control over the microstructure at the nano‐ and mesoscales. Taking inspiration from biominerals, CaCO3 is coprecipitated with anionic diblock copolymer worms or vesicles to produce single crystals of calcite occluding a high density of the organic component. This approach can also be extended to generate complex structures in which the crystals are internally patterned with nano‐objects of differing morphologies. Extensive characterization of the nanocomposite crystals using high resolution synchrotron powder X‐ray diffraction and vibrational spectroscopy demonstrates how the occlusions affect the short and long‐range order of the crystal lattice. By comparison with nanocomposite crystals containing latex particles and copolymer micelles, it is shown that the effect of these occlusions on the crystal lattice is dominated by the interface between the inorganic crystal and the organic nano‐objects, rather than the occlusion size. This is supported by in situ atomic force microscopy studies of worm occlusion in calcite, which reveal flattening of the copolymer worms on the crystal surface, followed by burial and void formation. Finally, the mechanical properties of the nanocomposite crystals are determined using nanoindentation techniques, which reveal that they have hardnesses approaching those of biogenic calcites. Abstract : A bioinspired one‐pot method is presented which generates nanocomposites comprising copolymer vesicles and worms occluded within calcite single crystals. Detailed characterization of the nanocomposites shows that the microstructures of the host crystals are controlled by size, shape, and surface chemistry of their copolymer occlusions, giving rise to hardnesses comparable to many calcite biominerals.